Pengembangan Model Pembelajaran Cerita Wayang Berbasis Permainan - Al Fanny, Afifah; Sukoyo, Joko; Purnomo, Sucipto Hadi (Pusdikra Publishing, 2026)
This study aims to develop a learning model for wayang stories based on card games and wayang puzzles that is feasible, practical, and effective for implementation at the junior high school level. The background of this research is based on the condition that wayang story learning is still predominantly conventional, teacher-centered, and lacks student engagement. In addition, previous studies have mostly focused on developing instructional media without being supported by a systematic learning model framework, which has resulted in less effective learning outcomes. This research employs the Research and Development (R&D) method using the 3D development model, which consists of the define, design, and develop stages. The research procedures include needs analysis, learning model design, product development in the form of wayang card games and puzzles, and expert validation involving subject matter experts and instructional design experts. The research subjects consist of junior high school students who study wayang story materials. Data collection techniques involve questionnaire surveys to assess the feasibility and effectiveness of the developed learning model. The results indicate that the game-based wayang story learning model developed in this study is suitable and appropriate for classroom implementation. The model demonstrates unique characteristics by actively engaging both teachers and students, enhancing interaction, and creating an enjoyable learning environment. Therefore, this learning model is expected to serve as an innovative alternative for improving the teaching and learning of wayang stories at the junior high school level.